Analisis Green Marketing Terhadap Green Online Purchase Intentions Melalui Green Trust Sebagai Variabel Mediasi - Reina Riswanti Pertiwi; Kokom Komariah; Dicky Jhoansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Green marketing has now become an alternative strategy that can increase value for the company's business. Green trust that runs well to succeed green marketing and there will also be green online purchase intention for consumers. This study aims to determine whether Green Marketing affects Green Online Purchase Intention through Green Trust as a mediating variable on The Body Shop products in Sukabumi City. The sample of this study amounted to 200 respondents with SEM analysis techniques using AMOS software version 22. The results of this study indicate Green Marketing has a significant effect on Green trust, Green Trust does not have a significant effect on Green Online Purchase Intention, and Green Trust can mediate the relationship between Green Marketing and Green Online Purchase Intention for The Body Shop consumers in Sukabumi City.